Fiducial reference systems for time and coordinates in satellite altimetry. Issue 2 (15th July 2021) - Mertikas, Stelios P.; Donlon, Craig; Matsakis, Demetrios; Mavrocordatos, Constantin; Altamimi, Zuheir; Kokolakis, Costas; Tripolitsiotis, Achilles
Abstract: Time is the fundamental measurement in satellite altimetry and the key parameter in building and keeping up a long-term, consistent, and reliable record for monitoring changes in sea level. Over the years, different time scales, although interconnected, have been used in altimetry and also in satellite positioning. This sometimes leads to inexplicit descriptions and ambiguous use of time and orbit coordinates as well as of their transformations between various reference and measuring systems. Altimetry satellites, like Sentinel-3, CryoSat-2, Jason-3, HY-2A/-2B, IceSat-2, etc., observe and practically realize ranges by measuring time differences between the transmission and reception of an electromagnetic wave (either radar or laser at present). Similar principles apply for global navigation satellite systems and for their terrestrial reference systems upon which altimetry is linked and tied together. Yet, the "meter" of any terrestrial reference systems is also defined by time. This work seeks to establish a standard reference system for "time" and "coordinates" in an effort to reach uniform and absolute standardization for satellite altimetry. It describes various errors generated from differences, discontinuities and interactions in time, frequency, range, time tagging, and reference coordinate frames. A new approach, called "fiducial reference measurements for altimetry", is here given to examine ways to connect errors with metrology standards in order to improve the estimation of uncertainty budgets in ocean and water level observation by altimetry. Finally, the geocentric inertial reference system and the international atomic time are proposed in this paper for satellite altimetry observations and products.